Analytic representation of periodic solutions of linear differential systems - Kenzhebaev, K. K.; Laptinskii, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the problem of periodic solutions of linear differential systems with small parameter. We establish new conditions for the existence and uniqueness of periodic solutions of these systems, which can be efficiently verified.